Основні категорії теорії конкуренції - Другова, Олена Сергіївна; Амансеідов, Шамухаммет (НТУ "ХПІ", 2015)
У статті проаналізовані основні поняття теорії конкуренції. Систематизовано взаємозв’язок між дифеніціями конкурентний потенціал, конкурентоспроможність, конкурентні переваги. Згруповано основні ознаки поданих понять. Доведено, що конкурентоспроможність підприємства не є постійною властивістю і може виявлятися тільки порівняно з групою підприємств на певному ринковому сегменті.

The article analyzes the basic concepts of the theory of competition. Systematized relationship between difenitsiyami competitive potential, competitive position, competitive advantages. Grouped the main features presented concepts. It is proved that the company's competitiveness is not a permanent property of, and may be manifested only by comparison with the group of companies in a particular market segment.
The main categories of competition theory
Keywords: конкурентоспроможність; конкурентний потенціал; конкурентні переваги; конкурентний статус; competitiveness; competitive potential; competitive advantages